Flame Retardant Additives Used for Polyurea-Based Elastomers—A Review - W. Dukarski; I. Rykowska; P. Krzyżanowski; M. Gonsior (Fire, 2024)
The growing interest in modern polymer materials has targeted research on complex plastic coatings and the possibilities of modifying their features and properties during manufacturing. Today’s modern coatings, including polyurea and polyurethane, are among the most modern developed resins. Compared to other polymer coatings, they are distinguished by their versatility, strength, and durability. They undoubtedly represent the next step in the evolution of coatings. Advances in coating technology have also led to the development of spray, injection, and roto-cast application equipment, improving polyurea-based elastomers’ performance. For many years, there has been much interest in increasing the flame resistance of polymers. This is dictated by safety considerations and the increasing requirements for the flammability of plastics, the area of application of which is growing every year. This text attempts to provide an overview of current research on flame retardant composites. Particular attention was paid to polyurea (PU) and polyurea-based hybrids and the application areas of polyurea coatings. The paper defines flame retardants, discusses how they work, and presents the types of flame retardants and the current trends of their usage in the production of plastics.